Supporting caregiver employees: managers' perspective in Canada. Issue 1 (6th February 2017) - Sethi, Bharati; Williams, Allison; Ireson, Rachelle
Abstract : Purpose: There is a growing recognition that when employees who are caregivers lack the organizational support/resources to manage their paid work with care responsibilities, it could result in poor job performance, increase absenteeism, and have an impact on their well-being. Very little is known about managers' perceptions in supporting their employees through workplace initiatives such as caregiver-friendly workplace policies (CFWPs). The purpose of this paper is: to examine managers' experience(s) with employees that are engaged in formal paid care and informal care; to explore availability of CFWPs; and to explore managers' standpoints on offering CFWPs to support their employees. Design/methodology/approach: The authors draw on the findings from semi-structured qualitative interviews with 20 ( n =20) managers working in the health care sector in an urban-rural region in Ontario, Canada. Findings: Intersectionality analysis of participant interviews revealed three key themes: managers' experiences with employees who are caregivers; knowledge and availability of CFWPs; and balancing business care with staff care. Practical implications: Data were drawn from health care sectors in one community in Ontario, Canada and may not generalize to other settings. The small sample size and purposive sampling further limits the generalizability of the findings. Social implications: Study findings can be applied to develop workplace policies and procedures that are responsive to workers who are providing unpaid care. Originality/value: This study contributes to limited literature on manager's perspectives in supporting employees through CFWPs.